Quitosana fúngica na produção de biomaterial membranoso modificado por plasma de descarga em barreira dielétrica (dbd) - Paiva, Weslley de Souza (2017)
The biopolymer chitosan is one of the most used biomaterials by the industry, and can be presented in the form of solution, gel, films and membranes. This polymer is mainly obtained from the carapace of crustaceans, but if it is not properly purified, it can carry many allergenic proteins, these allergenic proteins may make it unfeasible for people who are allergic to crustaceans. In materials science, it is of great importance to study ways of modifying materials, aiming at optimizing them. In the case of polymer materials, the atmospheric plasma appears as an alternative treatment without damaging the study material. In view of these factors, the present work aimed to extract chitosan from Rhizopus stolonifer fungus isolated from the caatinga biome soil; the production of membranous material; application of atmospheric plasma and characterization of post treatment material. After extraction of fungal chitosan, it was characterized by infrared with Fourier transform (FI-TR), X-ray diffraction, zeta potential, and molecular weight. To prepare the membrane, a solution of chitosan (0.3g) solubilized in 2% acetic acid (30mL) was made, stirred for 24 hours and filtered, after which the chitosan solution was packed in a Petri dish of size Medium for 24 hours, obtaining the membrane. The membranous material was treated with atmospheric plasma at a voltage of 15 and 30 kV at the times of 1, 5 and 10 minutes, with a frequency of 500 Hz. After the treatment, analyzes of atomic force microscopy, scanning electron microscopy, wettability, degradability and swelling were performed. The results showed that the dielectric barrier plasma (DBD) increased the wettability of the membrane, reducing its contact angle from 77.5º to 30.9º, the plasma promoted alteration was evidenced by the result of the atomic force microscopy, which demonstrated a Increase in mean membrane roughness, rising from 668.61 nm to 2118.78 nm. The results of degradation and swelling rate also showed modification by treatments. The degradation varied between 11 and 85% and the swelling rate between 25 and 85%. The results demonstrate efficiency in the chitosan extraction process, its transformation into membrane and, mainly, that the plasma in dielectric barrier changes the surface of the material. Thus, it favors its use in different applications in the biomedical area as: tissue regeneration, bone reintegration, transport of pharmaceutical molecules and controlled release of drugs